The Management of the Potential of the National Livestock Barn in the NapanTTU Border Area with a Sociogeographic Approach: Potential livestock barn, border area, FGD, Napan Village - Pamungkas, Bella Theo Tomi; Saragih, Fernando; Mundiarti, Vanida (Universitas Negeri Semarang, 2024)
The importance of developing border areas as one of the programs run by the government must be supported by existing potential. Livestock is one of the largest contributors to income for the community in Napan Village. The absence of a location as a potential for developing livestock barns in Napan Village is a problem. Therefore, it is necessary to determine whether the area has a potential for developing livestock barns in Napan Village. This study includes mixed-method research and methods using forum group discussions (FGD) and IDW. Key informants are the Head of Napan Village and the community. The conclusion of this study shows that the development of livestock barns in Napan Village is quite large because it is supported by the number and types of diverse livestock and the community agrees to develop livestock barns there. The location for developing livestock barns is obtained as wide as 2.11 km2. This great potential can give Napan Village the potential for development in border areas, especially in the field of livestock. In addition, to overcome the problem of illegal livestock sales, it is necessary to build surveillance posts in border areas so that the number of incidents can be suppressed.